Question Number 125662 by physicstutes last updated on 12/Dec/20
$$\:\mathcal{I}\:=\:\underset{\mathrm{0}} {\overset{\mathrm{4}} {\int}}\:\mathrm{tanh}^{−\mathrm{1}} \:\mathrm{2}{x}\:{dx}\:=\:??? \\ $$
Answered by mathmax by abdo last updated on 12/Dec/20
$$\mathrm{th}\left(\mathrm{x}\right)=\mathrm{y}\:\Rightarrow\mathrm{y}=\frac{\mathrm{sh}\left(\mathrm{x}\right)}{\mathrm{ch}\left(\mathrm{x}\right)}=\frac{\mathrm{e}^{\mathrm{x}} −\mathrm{e}^{−\mathrm{x}} }{\mathrm{e}^{\mathrm{x}} \:+\mathrm{e}^{−\mathrm{x}} }\:=\frac{\mathrm{e}^{\mathrm{2x}} −\mathrm{1}}{\mathrm{e}^{\mathrm{2x}} +\mathrm{1}} \\ $$$$\mathrm{let}\:\mathrm{e}^{\mathrm{2x}} \:=\mathrm{u}\:\Rightarrow\frac{\mathrm{u}−\mathrm{1}}{\mathrm{u}+\mathrm{1}}=\mathrm{y}\:\Rightarrow\mathrm{u}−\mathrm{1}=\mathrm{yu}+\mathrm{y}\:\Rightarrow\left(\mathrm{1}−\mathrm{y}\right)\mathrm{u}=\mathrm{1}+\mathrm{y}\:\Rightarrow\mathrm{u}=\frac{\mathrm{1}+\mathrm{y}}{\mathrm{1}−\mathrm{y}} \\ $$$$\Rightarrow\mathrm{e}^{\mathrm{2x}} \:=\frac{\mathrm{1}+\mathrm{y}}{\mathrm{1}−\mathrm{y}}\:\Rightarrow\mathrm{2x}=\mathrm{ln}\left(\frac{\mathrm{1}+\mathrm{y}}{\mathrm{1}−\mathrm{y}}\right)\:\Rightarrow\mathrm{x}=\frac{\mathrm{1}}{\mathrm{2}}\mathrm{ln}\left(\frac{\mathrm{1}+\mathrm{x}}{\mathrm{1}−\mathrm{x}}\right)\:=\mathrm{th}^{−\mathrm{1}} \left(\mathrm{y}\right)\:\Rightarrow \\ $$$$\mathrm{th}^{−\mathrm{1}} \left(\mathrm{x}\right)=\frac{\mathrm{1}}{\mathrm{2}}\mathrm{ln}\left(\frac{\mathrm{1}+\mathrm{x}}{\mathrm{1}−\mathrm{x}}\right)\:\Rightarrow\mathrm{I}\:=\frac{\mathrm{1}}{\mathrm{2}}\int_{\mathrm{0}} ^{\mathrm{4}} \mathrm{ln}\left(\frac{\mathrm{1}+\mathrm{2x}}{\mathrm{1}−\mathrm{2x}}\right)\mathrm{dx} \\ $$$$\mathrm{we}\:\mathrm{do}\:\mathrm{the}\:\mathrm{changement}\:\frac{\mathrm{1}+\mathrm{2x}}{\mathrm{1}−\mathrm{2x}}=\mathrm{t}\:\Rightarrow\mathrm{1}+\mathrm{2x}=\mathrm{t}−\mathrm{2tx}\:\Rightarrow \\ $$$$\left(\mathrm{2}+\mathrm{2t}\right)\mathrm{x}=\mathrm{t}−\mathrm{1}\:\Rightarrow\mathrm{x}=\frac{\mathrm{t}−\mathrm{1}}{\mathrm{2}\left(\mathrm{t}+\mathrm{1}\right)}\:\Rightarrow\frac{\mathrm{dx}}{\mathrm{dt}}=\frac{\mathrm{1}}{\mathrm{2}}×\frac{\mathrm{t}+\mathrm{1}−\left(\mathrm{t}−\mathrm{1}\right)}{\left(\mathrm{t}+\mathrm{1}\right)^{\mathrm{2}} }=\frac{\mathrm{1}}{\left(\mathrm{t}+\mathrm{1}\right)^{\mathrm{2}} }\:\Rightarrow \\ $$$$\mathrm{I}\:=\frac{\mathrm{1}}{\mathrm{2}}\int_{\mathrm{1}} ^{−\frac{\mathrm{9}}{\mathrm{7}}} \mathrm{ln}\left(\mathrm{t}\right)\frac{\mathrm{dt}}{\left(\mathrm{t}+\mathrm{1}\right)^{\mathrm{2}} }\:\Rightarrow\:\mathrm{I}\:\mathrm{is}\:\mathrm{not}\:\mathrm{defined}\:\:….!: \\ $$